Research on Multiple Control Methods for Bionic Hands - Jiang Haolun (SHS Web of Conferences, 2022)
With the continuous development of society, the demand of patients for highly accurate and intelligent bionic hands has been increasing, and the control of bionic hands has been greatly improved at this stage, but it is still lacking in precision and sensitivity, and the manufacturing cost is also high. This paper focuses on the most mainstream research on various control methods for bionic hand, lists the specific advantages and disadvantages of different control methods by reading the literature, summarizing and comparing them, and making an in-depth prediction on the future development of the bionic hand. In conclusion, the control mode of the bionic hand still needs to be further studied and combined with different control modes to solve existing problems.